Sosialisasi Sertifikasi Halal Self Declare bagi Usaha Mikro Kecil di Desa Pelitaasih Kabupaten Garut: - - Nursiwan, Asep; Ryasid, Reza Nur Arif; Haerani, Yusni Diana (Attamkiim: Jurnal Pengabdian Masyarakat, 2025)
The rapid growth of the global halal industry makes halal certification a crucial prerequisite for Micro and Small Enterprises (UMKs) to expand market access and enhance competitiveness, particularly in Indonesia as the country with the largest Muslim population. However, many UMKs, especially in rural areas like Pelitaasih Village, Garut Regency, face significant challenges due to a lack of understanding about the halal certification process, including the simplified self-declare scheme facilitated by the government’s Free Halal Certification (SEHATI) program. This community service activity aimed to bridge this information gap and increase UMK participation in the SEHATI program. The methodology employed a mixed-methods approach with a one-group pre-experimental pre-test post-test design, involving culinary UMK operators in Pelitaasih Village. The intervention comprised comprehensive socialization, practical training, and individual consultations, designed based on principles of persuasive communication, social learning, and active learning to build understanding and skills. Evaluation was conducted by comparing pre-test and post-test scores to measure knowledge gain, and by recording the number of UMKs expressing interest or initiating the certification registration process after the activity. The results showed a significant increase in UMKs’ understanding of self-declare halal certification and the SEHATI program, reflected in the improved average post-test scores compared to pre-test. Furthermore, there was a clear increase in the number of UMKs expressing interest in registering for halal certification after participating in the program. The high enthusiasm among participants indicates a strong need for direct information and mentoring. These findings support the effectiveness of targeted socialization and mentoring in raising awareness and motivating UMK participation. The conclusion drawn from this community service is that comprehensive and practical socialization and mentoring are effective in increasing the understanding and encouraging the participation of rural UMKs in self-declare halal certification programs like SEHATI. From an Islamic economic perspective, this increased participation contributes to strengthening the local halal ecosystem, enhancing maslahah (public benefit) for consumers, and promoting the economic falah (well-being) of UMKs. The SEHATI program holds great potential, and its success depends on robust grassroots implementation strategies. Continued mentoring and expanding program reach to other areas are recommended.